2009
DOI: 10.1039/b819148d
|View full text |Cite
|
Sign up to set email alerts
|

1,6-Dimethyl-4-hydroxy-3-pyridinecarboxylic acid and 4-hydroxy-2-methyl-3-pyridinecarboxylic acid as new possible chelating agents for iron and aluminium

Abstract: 1,6-Dimethyl-4-hydroxy-3-pyridinecarboxylic acid (DQ716) and 4-hydroxy-2-methyl-3-pyridinecarboxylic acid (DQ2) were evaluated for possible application to iron (Fe) and aluminium (Al) chelation therapy. Metal/ligand solution chemistry, electrochemistry, cytotoxicity, octanol/water partitioning (D(o/w)), and chelation efficiency, were studied. The Fe(iii)/DQ716, Fe(iii)/DQ2, Al(iii)/DQ716, and Al(iii)/DQ2 solution chemistry was investigated in aqueous 0.6 mol kg(-1) (Na)Cl at 25 degrees C by means of potentiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…No useful ESI‐MS signals were observed working in negative ion mode, apart from those of deprotonated DQ716 ( m / z 166) and, when added, of CF 3 COO − ( m / z 113). The absence of negative peaks related to Al(III)/DQ716 complexes was expected, as in solution they are neutral or positively charged 10. Therefore, all spectra were obtained in positive ion mode.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No useful ESI‐MS signals were observed working in negative ion mode, apart from those of deprotonated DQ716 ( m / z 166) and, when added, of CF 3 COO − ( m / z 113). The absence of negative peaks related to Al(III)/DQ716 complexes was expected, as in solution they are neutral or positively charged 10. Therefore, all spectra were obtained in positive ion mode.…”
Section: Resultsmentioning
confidence: 99%
“…The NH(CH 2 CH 3 ) + peak (at m/z 102.131) is not observable at acidic pH but it becomes predominant at higher pH, as the solutions were basified by triethylamine additions. The absence of peaks related to the 1:1 aluminium‐ligand complex (AlL 2+ ), and the presence of a minor peak due to a dimer, are the qualitative differences observed between the results of ESI‐MS and of equilibrium techniques 10…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies on the design, synthesis and complex formation equilibria of variously substituted hydroxypyridinecarboxylic acids have been presented by the group of Di Marco: these ligands are characterized by two coordinating groups (-OH and -COOH) in various positions (2,3; 3,2; 3,4; 4,3) and differently methylated. [50][51][52][53][54][55] A study of our group on bisphosphonate ligands showed their high efficiency as iron chelating agents, reaching pFe values higher than that of deferiprone. 56 To further improve bisphosphonate chelating properties the conjugation with other strong coordinating groups was proposed.…”
Section: Recent Research Achievements On Iron Chelating Agentsmentioning
confidence: 99%